MENINGKATKAN MINAT BELAJAR PESERTA DIDIK DENGAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING PADA MATERI MATEMATIKA KELAS IV SD - Novi Setianingsih; Sukamto; Choirul Huda (STKIP Subang, 2023)
The aim of this study is the result of growing interest in learning participants in math subjects and in growing interest in learning participants using the based learning problem model (PBL). This type of research is a class action study that adaptes the Kurt lewin model (planning, acting, observing, and reflecting) that Kurt lewin popularized. Kela's actions research subject is 22 student. Data is obtained through observation, angket, and documentation. Research indicates that the model for learning problems based learning can increase interest in learning mathematics participants. The increased interest in learning participants from earlier conditions, cycles I, and cycles ii has achieved or surpassed the researchers' target of success. At the beginning the average interest in learning participants was 69 in the category of considerable interest with the percentage of learners getting 72%. The participants' learning interest is on the I cycle with an average of 83 in the category of interest with the student presentation getting 95%. Whereas the results of studying cycle ii with an average of 90 in the category are very interested in the percentage of learners who are sufficiently interested above get 100%